Paisagens cársticas de Formosa, Goiás : um estudo para a geodiversidade - Santos, Suzana Moura dos (2025)
The introduction to this work highlights the importance of preserving the karst l andscapes in Formosa, Goiás, emphasizing their unique geological and geographic characteristics. These landscapes, which include formations such as caves and sinkholes, are presented as a natural heritage site. They require protection due to their beauty a nd rarity, along with the crucial role they play in the well being of the community and future generations. The geodiversity of these areas is highlighted, demonstrating how they support a specific biodiversity, providing habitat for species that have adap ted to these unique conditions. The preservation of these karst landscapes is seen as essential to maintaining the ecological richness of the region, ensuring that future generations can enjoy and learn from these environments. The dissertation suggests th e need for more detailed research on local geodiversity, along with the implementation of robust environmental education programs. These programs aim to increase public awareness of the value of these areas, encouraging conservation and sustainable managem ent. The research objectives include the identification and characterization of Formosa's main karst formations. The goal is to analyze the challenges of their preservation and promote development. Furthermore, we seek to raise social awareness about the i mportance of protecting these natural environments, ensuring their conservation and preservation for future generations.